FRI0379 Salivary Metabolomics of Primary SjÖGren's Syndrome. (10th June 2014) - Kageyama, G.; Saegusa, J.; Tanaka, S.; Takahashi, S.; Nishida, M.; Tsuda, K.; Yamamoto, Y.; Okano, T.; Akashi, K.; Nishimura, K.; Sendo, S.; Kogata, Y.; et al.
Abstract : Background: Primary Sjögren's syndrome (pSS) is an autoimmune exocrinopathy characterised by the infiltration of mononuclear cells into salivary and lacrimal glands leading to destruction of the parenchymal tissue and causing oral and ocular dryness. Omics studies such as genomics, proteomics and metabolomics have been extensively used to elucidate biological mechanisms of diseases through collective characterization and quantification of pools of biological molecules and generating molecular profiles for biospecimens. Saliva contains a variety of informative substances which may closely reflect the pathogenetic process of pSS in salivary glands. In fact, salivary proteomics from pSS patients have detected some proteins as biomarkers for pSS diagnosis. To date, metabolomics has been widely conducted and is regarded as the end point of "omics cascade" and most predictive of phenotype. However, salivary metabolomics from pSS patients has not been reported up-to-date. Objectives: To compare the salivary metabolite profile between patients with pSS and healthy control (HC) subjects. Methods: We obtained saliva from 12 female pSS patients (mean age 44.2±13.01) and 21 age-matched female HCs by spitting for 15 minutes. The metabolite profile of saliva specimens were analyzed by gas chromatography-mass spectrometry. The levels of metabolites were calibrated by saliva volume per 15 minutes enabling us to compare the metabolite production level of whole salivary glands for 15 minutes. Results: 88 metabolites were detected by our system. 32 metabolites were decreased and only one metabolite was increased in pSS patients. Principal component analysis (PCA) revealed a loss in salivary metabolite diversity in pSS patients compared to HCs. The decrease of Glysine, Tyrosine, Uric Acid and Fucose which may reflect the destruction of salivary gland due to chronic sialoadenitis contributed to the loss of diversity. PCA amongst pSS patients revealed that pSS could be divided into two subpopulations according to their metabolite profiles and the prevalence of major salivary glanditis was different between the two subpopulations (p=0.014). Conclusions: In this preliminary study, the salivary metabolite profile of pSS patients was less diverse compared to controls. Salivary metabolite profile was affected by the presence of major salivary glanditis suggesting that salivary metabolomics may serve as a prospective approach to discover the underlying pathogenesis of pSS. Disclosure of Interest: None declared DOI: 10.1136/annrheumdis-2014-eular.1201